2018
DOI: 10.3389/fbioe.2018.00147
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on Improving Environmental Monitoring of Biothreats

Abstract: For more than a decade, the United States has performed environmental monitoring by collecting and analyzing air samples for a handful of biological threat agents (BTAs) in order to detect a possible biological attack. This effort has faced numerous technical challenges including timeliness, sampling efficiency, sensitivity, specificity, and robustness. The cost of city-wide environmental monitoring using conventional technology has also been a challenge. A large group of scientists with expertise in bioterror… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…On the other hand, systematic environment monitoring for all diseases is, for now, impossible due to technological barriers and cost challenges. Experts in biodefense suggested that more targeted measurements in delimited spaces or during a large gathering of people should be the priority to improve the sensitivity and specificity of the early detection of a biological attack but, also for a natural outbreak, while reducing the cost [ 51 ]. For example, the analysis of wastewater could be a good way to monitor the spread of SARS-CoV-2 in the community [ 52 ].…”
Section: How To Early Detect the Unexpected?mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, systematic environment monitoring for all diseases is, for now, impossible due to technological barriers and cost challenges. Experts in biodefense suggested that more targeted measurements in delimited spaces or during a large gathering of people should be the priority to improve the sensitivity and specificity of the early detection of a biological attack but, also for a natural outbreak, while reducing the cost [ 51 ]. For example, the analysis of wastewater could be a good way to monitor the spread of SARS-CoV-2 in the community [ 52 ].…”
Section: How To Early Detect the Unexpected?mentioning
confidence: 99%
“…For example, the analysis of wastewater could be a good way to monitor the spread of SARS-CoV-2 in the community [ 52 ]. However, these measurements should always be paired with epidemiological investigations to avoid any misinterpretation of the results [ 51 ].…”
Section: How To Early Detect the Unexpected?mentioning
confidence: 99%
“…The second possible case would be an intentional design or release of toxic proteins for biological attack 7 . To prevent release of toxic proteins, there are ongoing efforts to build systems and devices that collect unknown proteins or organisms together that identify proteins with potential harm 811 . There is a strong demand for such systems for lab facilities of gene synthesis, places where many people gather, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…T he public health challenges of the 21st century, such as emerging infectious diseases, biological threats, climate change, unhealthy lifestyles, and living conditions, [1][2][3][4] require local and global readiness to respond to the population's needs by strengthening human resources, quality, and safety. 5 According to European Centre for Disease Prevention and Control (ECDC), the level of public health microbiology system capabilities and capacities in 30 Europe Union countries measured by the aggregated EULabCap index varies from the low and moderate to high level, 6 while only a few countries in the Western Balkan report full public health microbiology system capacity for rare and emerging diseases, such as smallpox, severe acute respiratory syndrome (SARS), and yellow fever.…”
mentioning
confidence: 99%